Cognitive Behavioural Coaching : A Guide to Problem-Solving and Personal Development - Neenan, Michael, ....-; Dryden, Windy, 1950- (London : Routledge, 2020)
The way we think profoundly influences the way we feel and behave. Therefore, it can be said that learning to think differently can enable us to feel and act differently. Derived form the methods of cognitive behaviour therapy, Cognitive Behavioural Coaching: A Guide to Problem-Solving and Personal Development shows you how to help yourself by tackling self- and goal-defeating thinking and replacing it with an effective problem-solving outlook.
Keywords: coaching; cognitieve gedragstherapie